2005
DOI: 10.1097/01.don.0000167395.61075.38
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Double-Blind Comparison of Bupivacaine and Lidocaine for Inferior Alveolar Nerve Blocks

Abstract: The purpose of this prospective, randomized, double-blind study was to compare the degree of pulpal anesthesia obtained with 0.5% bupivacaine with 1:200,000 epinephrine and 2% lidocaine with 1:100,000 epinephrine in inferior alveolar nerve blocks. Using a crossover design, inferior alveolar nerve blocks were randomly administered, in a double-blind manner, using 0.5% bupivacaine with 1:200,000 epinephrine and 2% lidocaine with 1:100,000 epinephrine, at two separate appointments, to 39 subjects. A pulp tester w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 19 publications
4
59
0
6
Order By: Relevance
“…In the study by Gregorio et al (14), reinforcement was necessary in 14% of surgeries performed with bupivacaine and 2% of those performed with articaine, this difference was significant. It has been shown that bupivacaine is less effective in infiltrative techniques, due to its high lipid solubility which also makes the position of the needle key (4,6,11). This could explain the difference found in the work by Gregorio et al (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Gregorio et al (14), reinforcement was necessary in 14% of surgeries performed with bupivacaine and 2% of those performed with articaine, this difference was significant. It has been shown that bupivacaine is less effective in infiltrative techniques, due to its high lipid solubility which also makes the position of the needle key (4,6,11). This could explain the difference found in the work by Gregorio et al (14).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its diverse pathology, third molar extraction is one of the most common surgical procedures in oral surgery, and is generally accompanied by postoperative discomfort, leading to the intake of analgesics, anti-inflammatories and antibiotics, and sometimes absenteeism from work. It has been suggested that the longer duration of action of bupivacaine associated with the residual analgesia and the gradual onset of pain, may reduce the need for analgesics, which could be interesting given the side effects that these are associated with (3)(4)(5)(11)(12)(13). This study aims to compare the efficacy and safety of bupivacaine and articaine as local anesthetics for the extraction of mandibular third molars, and verify whether bupivacaine produced residual analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed an observable increase in pain levels at 4-hrs in both groups compared to the immediate post-operative pain levels, this may be related to the loss of local anesthetic effect (27) . This was in agreement with the results of Gondim et al (2010) (8) and Al-Zaka (2012) (9) that showed that the highest levels of pain occurred at 0-4-hrs and then decreased at 24 and 48-hrs.…”
Section: Root Canal Treatment Was Completed In a Single-visit As Wongmentioning
confidence: 58%
“…Large number of studies were done to compare the efficacy of bupivacaine with other amide local anesthetics such as lidocaine. The anesthetic efficacy of bupivacaine hydrochloride was more compared to lidocaine hydrochloride and was effective in postoperative pain management [17]. Many studies reported that the combination of lidocaine hydrochloride with long acting local anesthetic will increase the duration of action and decrease patient discomfort [18].…”
Section: Discussionmentioning
confidence: 99%